A new insight into the evolution and functional divergence of FRK genes in Pyrus bretschneideri. Issue 7 (18th July 2018) - Cao, Yunpeng; Li, Shumei; Han, Yahui; Meng, Dandan; Jiao, Chunyan; Abdullah, Muhammad; Li, Dahui; Jin, Qing; Lin, Yi; Cai, Yongping
Abstract : In plants, plant fructokinases (FRKs) are considered to be the main gateway of fructose metabolism as they can phosphorylate fructose to fructose-6-phosphate. Chinese white pears ( Pyrus bretschneideri ) are one of the popular fruits in the world market; sugar content is an important factor affecting the quality of the fruit. We identified 49 FRKs from four Rosaceae species; 20 of these sequences were from Chinese white pear. Subsequently, phylogenic relationship, gene structure and micro-collinearity were analysed. Phylogenetic and exon–intron analysis classified these FRK s into 10 subfamilies, and it was aimed to further reveal the variation of the gene structure and the evolutionary relationship of this gene family. Remarkably, gene expression patterns in different tissues or different development stages of the pear fruit suggested functional redundancy for PbFRKs derived from segmental duplication or genome-wide duplication and sub-functionalization for some of them. Additionally, PbFRK11, PbFRK13 and PbFRK16 were found to play important roles in regulating the sugar content in the fruit. Overall, this study provided important insights into the evolution of the FRK gene family in four Rosaceae species, and highlighted its roles in both pear tissue and fruits. Results presented here provide the appropriate candidate of PbFRK s that might contribute to fructose efflux in the pear fruit.